THE EFFECTS OF GAMES ON VOCABULARY LEARNING AMONG 11th GRADE STUDENTS AT NGUYEN THI MINH KHAI HIGH SCHOOL - Phung, Thi Thanh Huyen (2020)
Using games to teach vocabulary to high school students is one of the most efficient ways. However, whereas many advocates of vocabulary games give evidence about a variety of their advantages, others subscribe to the opposite ideas. This paper will aim at enlightening both pros and cons of vocabulary games. Firstly, this study will investigate into the overall current situation of vocabulary games in grade 11 at Nguyen This Minh Khai high school. Then, a deep exploration of favorable and adverse influence of vocabulary games on teachers and students there will be provided. Furthermore, the researcher also offers many pedagogical recommendations to enhance benefits as well as limiting the problems of games. For the accomplishment of these purposes, 10 teachers and 111 students were surveyed by the questionnaires, three classroom observations were made and 3 teachers and 6 students were interviewed. Afterwards, data analysis were conducted with the combination of table, bar chart, typical quotes, pictures and observation checklists in order to seek for the last answers to three research questions. To conclude, major findings, final recommendations, strengths and weaknesses of the study and suggestions for further research will be stated.